Emancipation or Enclosement? The Spatialization of Difference and Urban Ethnic Contestation in Colombia (2012)
The focus of this article is a paradox inherent in the political effects of spatial claims undertaken by multicultural policies in many nation states: though territory is considered as one of the primary means of achieving autonomy and self-determination, it is at the same time a mechanism that encloses difference. Through a combination of archival and ethnographic research I study the political effects of binding indigenous people's minority rights with indigenous reservations in Colombia. I focus on analyzing the legal ways in which an 'ethnic indigenous type' has been attached to an 'ethnic indigenous rural topos' in the jurisprudence of the Colombian Constitutional Court. I also examine how ethnic groups in the capital city of Bogotá have questioned the multicultural ideals of indigeneity and the romantic desires of what an indigenous place should look like. Ultimately, my intention is to draw attention both analytically and politically, to the necessity of more thorough analyses of the consequences of strict forms of spatializing ethnicity. © 2011 The Author Antipode © 2011 Antipode Foundation Ltd.